Sources about the Rulers of the Chancellery of Turkestan Governor General - Kenjayev Nurolim Jumanazarovich (Zien Journals, 2023)
In the system of the Military People's Administration of the Turkestan General Government, the office of the Governor General was the heart of this colonial body, then its Rulers can be considered the think tank. According to the regulations of July 11, 1867, all employees of the General Government were to be appointed from among the military personnel, who, in the conditions of Turkestan, clerical military ranks were to perform the duties of civilian ranks. Naturally, when the geopolitical location of the General Government changed, Regulations were adopted by the Regional Administration. All Regulations, without exception, specified the scope of activity of the Office of the Governor General.
Keywords: specified; Government; Regional; geopolitical